2021
DOI: 10.1111/csp2.443
|View full text |Cite
|
Sign up to set email alerts
|

Variable effects of protected areas on long‐term multispecies trends for Australia's imperiled birds

Abstract: Protected areas are important for preventing biodiversity declines, yet indicators of species' trends in protected areas rarely include threatened species. We use data from the first national Threatened Species Index developed in Australia to report on trends for threatened and near‐threatened birds inside and outside terrestrial and marine protected areas. We adopted the Living Planet Index to calculate trends for 39 bird taxa at 16,742 monitoring sites (11,539 inside and 5,203 outside PAs) between 1985 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 77 publications
(98 reference statements)
0
0
0
Order By: Relevance
“…In addition, existing ecological vulnerability information should be combined with other environmental indicators based on monitoring, such as species monitoring based on standardized surveys. Tulloch et al [77] (2023) showed that different monitoring and management strategies have long-term impacts on endangered animals; Bayraktarov et al [78] (2021) argue that strengthening active management and monitoring of protected areas to track and report long-term trends across species is important for preventing biodiversity decline. Therefore, in future ecological vulnerability research, it can be combined with the monitoring of additional environmental indicators.…”
Section: Shortcomings and Prospectsmentioning
confidence: 99%
“…In addition, existing ecological vulnerability information should be combined with other environmental indicators based on monitoring, such as species monitoring based on standardized surveys. Tulloch et al [77] (2023) showed that different monitoring and management strategies have long-term impacts on endangered animals; Bayraktarov et al [78] (2021) argue that strengthening active management and monitoring of protected areas to track and report long-term trends across species is important for preventing biodiversity decline. Therefore, in future ecological vulnerability research, it can be combined with the monitoring of additional environmental indicators.…”
Section: Shortcomings and Prospectsmentioning
confidence: 99%
“…Ultimately, for optimal ecological outcomes, PAs need to be strategically located in order to protect high-quality habitat, which is not the norm in most parts of the world (Venter et al 2018). As a result, the effectiveness of PAs in terms of wildlife conservation is sometimes hard to predict, and recent studies have recorded counterintuitive effects of PAs in several taxa: similar densities inside and outside PAs (no PA effect) or even negative population trends inside PAs (Kiffner et al 2020;Terraube et al 2020;Bayraktarov et al 2021).…”
Section: Introductionmentioning
confidence: 99%